Football boot insoles and sensitivity to extent of ankle inversion movement - Waddington, G.; Adams, R. (British Journal of Sports Medicine, 2003)
Background: The capacity of the plantar sole of the foot to convey information about foot position is reduced by conventional smooth boot insoles, compared with barefoot surface contact.